2021
DOI: 10.1108/pr-04-2020-0255
|View full text |Cite
|
Sign up to set email alerts
|

Organizational identification of knowledge workers in India: causes, consequences and the relevance of context

Abstract: PurposeThis research develops and tests a model for organizational identification (OID) in a sample of knowledge workers in India. It calls attention to the relational antecedents of OID that are often overlooked in existing literature. Strong theoretical arguments are also built for context-specific outcome behaviors such as intrinsic motivation (IM) and innovative work behavior (IWB) that are relevant to knowledge work.Design/methodology/approachData were collected from 357 IT industry employees in India. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 100 publications
(130 reference statements)
2
5
0
Order By: Relevance
“…The results reveal the direct and indirect effects of resonant leadership on work performance and turnover intention (Gaan & Shin, 2022;Sahu et al, 2018;Squires et al, 2010;Wagner et al, 2013). Furthermore, the findings indicated that self-efficacy (Bayraktar & Jiménez, 2020;Jayathilake et al, 2021;Reddy & Dawlinmaria, 2020;Singh et al, 2018) and organizational identification (Chillakuri & Mahanandia, 2018;Mazumder et al, 2021;Shen et al, 2014;Walumbwa et al, 2011) mediated the leadership process significantly and positively (Afzal et al, 2019;Suifan et al, 2020). Thus, the findings of this study concur, to some extent, with the results of the extant literature.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The results reveal the direct and indirect effects of resonant leadership on work performance and turnover intention (Gaan & Shin, 2022;Sahu et al, 2018;Squires et al, 2010;Wagner et al, 2013). Furthermore, the findings indicated that self-efficacy (Bayraktar & Jiménez, 2020;Jayathilake et al, 2021;Reddy & Dawlinmaria, 2020;Singh et al, 2018) and organizational identification (Chillakuri & Mahanandia, 2018;Mazumder et al, 2021;Shen et al, 2014;Walumbwa et al, 2011) mediated the leadership process significantly and positively (Afzal et al, 2019;Suifan et al, 2020). Thus, the findings of this study concur, to some extent, with the results of the extant literature.…”
Section: Discussionsupporting
confidence: 85%
“…In the context of SIT and SET (van Knippenberg & Schippers, 2007), it is argued that employees with a desire to identify with the organization (Mazumder et al, 2021) work towards goals with higher efficiency and potential (Bakotic, 2016;Jiang & Law, 2013;Mazumder et al, 2021;Singh et al, 2018). Thus, through fulfilling their entrepreneurial orientations based on the trust established by the leaders, Gen-Z employees feel more obliged to stay with the organization.…”
Section: The Mediating Role Of Organizational Identificationmentioning
confidence: 99%
See 3 more Smart Citations